A new regulator RsdA mediating fungal secondary metabolism has a detrimental impact on asexual development in Pestalotiopsis fici. (17th December 2018) - Zhou, Shuang; Zhang, Peng; Zhou, Haichuan; Liu, Xingzhong; Li, Shu‐Ming; Guo, Liangdong; Li, Kuan; Yin, Wen‐Bing
Summary: Secondary metabolite (SM) production and development are correlated processes in fungi that are often coordinated by pleiotropic regulators. The eukaryotic regulators are critical players in mediating SM production related to fungal development, yet little data are available to support this hypothesis. In this study, a global regulator, RsdA (r egulation ofs econdary metabolism andd evelopment), was identified through genome‐wide analysis and deletion of the regulator gene in the endophytic fungus Pestalotiopsis fici . Here, we established that RsdA regulation of SMs is accompanied by the repression of asexual development. Deletion of rsdA significantly reduces not only asexual development, resulting in low sporulation and abnormal conidia, but also the major SM production, while remarkably increasing the melanin production. Overproduction of melanin leads to the formation of unusual, heavily pigmented hyphae. Transcriptome analysis data provide the evidence that RsdA globally regulates genes involved in secondary metabolism and asexual development. Double deletion of rsdA and the melanin polyketide synthase gene PfmaE confirm that RsdA regulation of asexual development is independent of the melanin biosynthetic pathway. Finally, our results demonstrate that RsdA can be used for the discovery of secondary metabolites in filamentous fungi.